2013
DOI: 10.1537/ase.120813
|View full text |Cite
|
Sign up to set email alerts
|

Tail length estimation from sacrocaudal skeletal morphology in catarrhines

Abstract: Tail morphology in primates is important for interpreting functional adaptation and phylogeny. Tail length is probably the most remarkable trait. Establishing usable methods to predict the tail length of extinct primates is part of the basis for the reconstruction of primate evolution, particularly of hominoids. Previous studies revealed that sacral morphology often predicts tail length. However, most previous studies have only attempted this by using categories (short, long, etc.). A problem with those studie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Given this, the presence of well-developed mammillo-articular processes in extant species with long tails would suggest the inclusion of L. vallesiensis in this group. Russo and Shapiro (2011) on their study on primates, found that the development of the caudal transverse process of the sacrum separated "long" and "tailless" groups from the "short"/"very short" groups, although the study did not distinguish "short" and "very short" groups (Tojima 2013). In the case of our compared sample of felines, there is no clear relationship between the morphology of the caudal transverse process and the length of the tail, as for example Le.…”
Section: Sacrummentioning
confidence: 98%
“…Given this, the presence of well-developed mammillo-articular processes in extant species with long tails would suggest the inclusion of L. vallesiensis in this group. Russo and Shapiro (2011) on their study on primates, found that the development of the caudal transverse process of the sacrum separated "long" and "tailless" groups from the "short"/"very short" groups, although the study did not distinguish "short" and "very short" groups (Tojima 2013). In the case of our compared sample of felines, there is no clear relationship between the morphology of the caudal transverse process and the length of the tail, as for example Le.…”
Section: Sacrummentioning
confidence: 98%
“…1 . The caudal vertebrae are part of the skeletal system that maintains the tail, which articulates posterior to the sacrum [ 28 ]. The morphology of the caudal vertebrae differs between the proximal and distal regions [ 2 , 3 , 13 , 22 , 29 ].…”
Section: What Is a Tail?mentioning
confidence: 99%
“…Other studies have addressed the relationship between sacral morphological variation and tail length variation or body size. The caudal part of the sacrum (especially the final sacral vertebrae) tends to show morphological variations that reflect the number of caudal vertebrae articulating posteriorly and/or caudal musculature attaching to the sacrum (Ankel, 1965, 1972; Russo & Shapiro, 2011; Tojima, 2013, 2014, 2015; Ward et al, 1991). Most of these studies were aimed at fossilized samples to reconstruct the tail length of extinct species categorically or quantitatively.…”
Section: Introductionmentioning
confidence: 99%